PERAN SITUS BERSEJARAH DALAM PEMBELAJARAN SEJARAH: Studi Kasus di Situs Makam Po Teumeureuhom Aceh Jaya - alfadhil, Musa; Samwil; Sopar; Khairan; Asra, Saiful (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2025)
Abstract Learning history through historical sites, like the Poe Teumeureuhom tomb in Aceh Jaya, can boost students' historical awareness by connecting lessons to relevant local history. However, this study found that even though these historical sites are close to several schools, activities that involve visiting them for history lessons are quite rare. The lack of integration of local history into the curriculum and the underutilization of historical sites as learning resources diminish students' understanding of their cultural identity. By using a site-based learning approach, students can learn history not just through theory but also by directly appreciating local historical values. This article suggests several steps to address these issues, such as incorporating local history into the curriculum, using technology to spread historical information, and organizing educational pilgrimage activities. The goal is to strengthen historical awareness and enhance pride in cultural heritage among students in Aceh Jaya.